Editors' Choice of Noteworthy Clinical Endoscopy Publications in the First Decade - Gwang Ha Kim; Kwang An Kwon; Do Hyun Park; Jimin Han (Clinical Endoscopy, 2021)
This is a special review to celebrate the 10th anniversary of Clinical Endoscopy. Each deputy editor has selected articles from one’s subspecialty that are significant in terms of the number of downloads, citations, and clinical importance. The articles included original articles, review articles, systematic reviews, and meta-analyses.